2006
DOI: 10.1002/aoc.1145
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and evaluation of novel ferrocene‐substituted triadimenol analogues

Abstract: In search of potent 1H-1,2,4-triazole derivatives with improving antifungal activity, a class of novel ferrocene-triadimenol analogues was synthesized and their biological potential evaluated. Screening data revealed that these new derivatives did not have the antifungal activities of parent compounds, but showed unexpectedly promising plant growth regulatory activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Unfortunately, analogue 1 showed no growth inhibition on the studied fungi (C. albicans, C. glabrata, C. parapsilosis, and C. krusei). 46 Fang and co-workers prepared a wide variety of ferrocene derivatives containing 1,2,4-triazole, thiazole or both, such as ferrocenyl-substituted vinyl 1,2,4triazole derivatives (2Z, 2E), 47 ferrocene-triadimefon analogues (3), 48 ferrocene-triadimenol analogues (4), 49 1-ferrocenyl-3-aryl-2-(1H-1,2,4-triazol-1-yl)-prop-2-en-1-one derivatives (5, Fig. 5), 50 and N-substituted benzylidene-4-ferrocenyl-5-(1H-1,2,4-triazol-1-yl)-1,3-thiazol-2-amine derivatives (6, Fig.…”
Section: Metallocenyl-derivatives Of Azole Antifungal Drugsmentioning
confidence: 99%
“…Unfortunately, analogue 1 showed no growth inhibition on the studied fungi (C. albicans, C. glabrata, C. parapsilosis, and C. krusei). 46 Fang and co-workers prepared a wide variety of ferrocene derivatives containing 1,2,4-triazole, thiazole or both, such as ferrocenyl-substituted vinyl 1,2,4triazole derivatives (2Z, 2E), 47 ferrocene-triadimefon analogues (3), 48 ferrocene-triadimenol analogues (4), 49 1-ferrocenyl-3-aryl-2-(1H-1,2,4-triazol-1-yl)-prop-2-en-1-one derivatives (5, Fig. 5), 50 and N-substituted benzylidene-4-ferrocenyl-5-(1H-1,2,4-triazol-1-yl)-1,3-thiazol-2-amine derivatives (6, Fig.…”
Section: Metallocenyl-derivatives Of Azole Antifungal Drugsmentioning
confidence: 99%
“…Moreover, quite often the same compounds revealed promising and somewhat unexpected plant growth regulatory activity. The synthesis is quite straightforward, starting from acetylferrocene, 1, [9][10][11][12][13][14][15] or ferrocenecarbaldehyde, 2, [16][17][18] and using classical organic reactions, as illustrated in Figures 3 and 4.…”
Section: Ferrocene-containing Agrochemicalsmentioning
confidence: 99%
“…By reducing analogs of triadimefon, the corresponding ferrocenyl analogs of triadimenol, 8, were obtained [13]. They were tested as indicated above for the triadimefon analogs and generally did not exhibit any antifungal activity (Table 1, entry 5); however, all of them showed excellent plant growth regulatory ability, even larger than the keto precursors.…”
Section: Ferrocene-containing Agrochemicalsmentioning
confidence: 99%
“…Recent studies have shown that the combination of biological active N-heterocyclic compounds such as pyrazolines and pyrazoles with ferrocene moiety can result in favorable change of biological properties [29][30][31][32][33][34] which is rationalized as being due to their different membrane-permeation properties and anomalous metabolism [35][36][37][38]. As mentioned earlier, although 2-pyrazolines are amongst the most intensely studied compounds; N-acetylated ferrocenyl-2-pyrazoline derivatives are relatively less explored [29,32].…”
Section: Introductionmentioning
confidence: 99%